Pendampingan Konseling Islami dalam Mengatasi Krisis Identitas Remaja di Era Digital - Suriyati Suriyati; Suriati Suriati; Muhlis Muhlis; Makmur Jaya Nur; Nur Masyhar Faizin Jafar; Riska Riska; Eril; Umar (LP2M Universitas Islam Ahmad Dahlan, 2026)
The development of digital technology has a significant impact on the identity formation process of adolescents. Exposure to social media, a culture of social comparison, and the unfiltered flow of information often trigger an identity crisis, which Erik Erikson, in his psychosocial developmental stage, calls identity versus role confusion. This community service program aims to implement an Islamic counseling program as a preventive and curative effort to help adolescents build a healthy identity in the digital age. The method used is a participatory approach through group counseling, individual counseling, and psychoeducation based on the values ​​of monotheism, tazkiyatun nafs (respect for the self), and moral development. The program is implemented through a needs assessment, mentoring sessions, and evaluation of changes in participants' attitudes and understanding. The expected outcomes are increased self-awareness, controlled digital media use, and the formation of a more stable self-identity grounded in Islamic values. With an integrative approach combining psychological and spiritual aspects, Islamic counseling has the potential to become an applicable intervention model in schools and communities.